A collaborative approach for spam detection - Sousa, Pedro (2010)
Electronic mail is nowadays one of the most important Internet networking services. However, there are still many challenges that should be faced in order to provide a better e-mail service quality, such as the growing dissemination of unsolicited e-mail (spam) over the Internet. This work aims to foster new research efforts giving ground to the development of novel collaborative approaches to deal with spam proliferation. Using the proposed system, which is able to complement other anti-spam solutions, end-users are allowed to share and combine spam filters in a flexible way, increasing the accuracy and resilience levels of anti-spam techniques.